PENEGAKAN HUKUM TERHADAP IMIGRAN ILEGAL YANG TIDAK MEMILIKI DOKUMEN BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN DI WILAYAH HUKUM KOTA PEKANBARU - Anida Hujjailah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The term immigration is a translation of the Dutch immigratie, which comes from the Latin immigration. Immigrants when entering Indonesian territory must have documents valid in accordance with the legislation in force in Indonesia as referred to in Article 8 ( 1 ) of Law Number 6 of 2011 on Immigration explained that everyone who entered and exit Indonesian territory is required to have a valid travel document and valid. In the city of Pekanbaru number of illegal immigrants is quite a lot so this is a phenomenon for the citizens of the city of Pekanbaru . This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or place in carefully. The research was done at the Immigration Office Class 1 Pekanbaru, while the sample population is a whole party relating to the issues researched in this study, the data source used, primary data, secondary data , and the data tertiary data collection techniques in this study by observation , interview and literature study From the research problem there are three things that can be inferred. First, that the enforcement of the Law on foreigners by the Immigration. Class I Pekanbaru has been running, but in terms mengimpelmentasikan legislation has not been optimal , things to face in law enforcement against illegal immigrants is not , the existence of a special law to overcome , efforts done in terms of overcoming barriers to enforcement against illegal immigrants is making a special law on illegal immigrants and make penjag late in the borders of Indonesia. Suggestions Writer namely the addition of operational funds , improve human resources and the government should make a special legislation that deal with illegal immigrants.Keywords: law-enforcement-against-illegal-immigrants